2022
DOI: 10.1093/trstmh/trac018
|View full text |Cite
|
Sign up to set email alerts
|

Neurological manifestations of Kyasanur Forest disease: a retrospective cohort study from South India

Abstract: Background Kyasanur Forest disease (KFD) is a viral zoonotic disease where patients present with febrile illness and haemorrhagic manifestations in the first phase. In a small fraction of patients, the fever may be biphasic. This study aimed to describe the neurological manifestations of patients with KFD in the first and second phases of the illness. Methods This is a retrospective cohort study of 297 patients admitted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…CNS involvement was also significantly common in KFD compared to other febrile illnesses. This is similar to previous studies that showed CNS involvement in the form of encephalitis or encephalopathy to be a common finding in patients with the first phase of KFD [11,12]. Conjunc- Notes: KFD-Kyasanur Forest Disease, Lymphadenopathy (Cervical lymph nodes palpable on clinical examination), Hepatosplenomegaly (enlarged liver or spleen on clinical examination), LRT involvement-Lower respiratory tract involvement (presence of dyspnoea, requirement of supplemental oxygen or infiltrate on Chest X-ray), myocarditis (clinical suspicion along with elevated troponin), CNS involvement-Central nervous system involvement (altered sensorium or neck signs), Raised HCT-Raised Haematocrit (more than 40), Leucocytosis (Total leucocyte count more than 11,000/ cu.mm), Leukopenia (Total leucocyte count of less than 4,000/ cu.…”
Section: N Discussionsupporting
confidence: 92%
“…CNS involvement was also significantly common in KFD compared to other febrile illnesses. This is similar to previous studies that showed CNS involvement in the form of encephalitis or encephalopathy to be a common finding in patients with the first phase of KFD [11,12]. Conjunc- Notes: KFD-Kyasanur Forest Disease, Lymphadenopathy (Cervical lymph nodes palpable on clinical examination), Hepatosplenomegaly (enlarged liver or spleen on clinical examination), LRT involvement-Lower respiratory tract involvement (presence of dyspnoea, requirement of supplemental oxygen or infiltrate on Chest X-ray), myocarditis (clinical suspicion along with elevated troponin), CNS involvement-Central nervous system involvement (altered sensorium or neck signs), Raised HCT-Raised Haematocrit (more than 40), Leucocytosis (Total leucocyte count more than 11,000/ cu.mm), Leukopenia (Total leucocyte count of less than 4,000/ cu.…”
Section: N Discussionsupporting
confidence: 92%
“…Adhikari Prabha et al reported altered sensorium in 45% and seizures in 24% [12]. Gupta et al [16] in a study of 297 patients, reported altered sensorium and seizures as the clinical symptoms and focal infarcts as the major radiological findings in the first phase. In the second phase, the common symptoms were cerebellar signs and vision abnormalities.…”
Section: Discussionmentioning
confidence: 99%